Improving the readiness and clinical quality of antenatal care - findings from a quasi-experimental evaluation of a performance-based financing scheme in Burkina Faso - Inke Appel; Julia Lohmann; Manuela De Allegri; Jean-Louis Koulidiati; Serge Somda; Paul Jacob Robyn; Hermann Badolo; Stephan Brenner (BMC, 2023)
Abstract Background While maternal mortality has declined globally, it remains highest in low-income countries. High-quality antenatal care (ANC) can prevent or decrease pregnancy-related complications for mothers and newborns. The implementation of performance-based financing (PBF) schemes in Sub-Saharan Africa to improve primary healthcare provision commonly includes financial indicators linked to ANC service quality indicators. In this study, we examine changes in ANC provision produced by the introduction of a PBF scheme in rural Burkina Faso. Methods This study followed a quasi-experimental design with two data collection points comparing effects on ANC service quality between primary health facilities across intervention and control districts based on difference-in-differences estimates. Performance scores were defined using data on structural and process quality of care reflecting key clinical aspects of ANC provision related to screening and prevention pertaining to first and follow-up ANC visits. Results We found a statistically significant increase in performance scores by 10 percent-points in facilities' readiness to provide ANC services. The clinical care provided to different ANC client groups scored generally low, especially with respect to preventive care measures, we failed to observe any substantial changes in the clinical provision of ANC care attributable to the PBF. Conclusion The observed effect pattern reflects the incentive structure implemented by the scheme, with a stronger focus on structural elements compared with clinical aspects of care. This limited the scheme's overall potential to improve ANC provision at the client level after the observed three-year implementation period. To improve both facility readiness and health worker performance, stronger incentives are needed to increase adherence to clinical standards and patient care outcomes.